The Effect of Profitability on Firm Value with Company Size as a Moderating Variable in the Industrial Sector in 2019-2021 - Rahma Aryani; Ira Hapsari; Amir; Selamet Eko Budi Santoso (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to examine the effect of profitability on firm value with firm size as a moderating variable. The population for this research is the industrial sector listed on the IDX in 2019-2021. The sampling technique used purposive sampling and obtained a number of 63 observational data from 21 companies. The data analysis technique uses multiple linear regression analysis with the Moderated Regression Analysis (MRA) test using the SPSS 25 program. The results of this research prove that profitability has a positive effect on firm value with a magnitude of 331.224. Meanwhile, company size is able to moderate the influence of profitability on firm value in a negative direction, which means it weakens with a magnitude of -12.252.